Persepsi keluarga terhadap peran perawat dalam pemenuhan kebutuhan dasar manusia pada pasien stroke - Nina Apriyanti, Sri Werdati dan Dwi Harjanto (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Stroke patients experience multi-dimensional problems, not only physical problems, which concern the degradation of body organ function but also psychological problems. These prevent stroke patients from fulfilling their basic requirements. Nurses have a very important role in this case. One method to assess the quality of treatment is by knowing the family perception. Objectives: This study aims at knowing data concerning the family perception to nurse role in basic requirement accomplishment of human being at stroke patients in RS. Dr. Soeradji Tirtonegoro – Klaten. Methods: This study is descriptive, using a cross sectional study approach. The data were collected by distributing questionnaires to stroke patient families at RS Dr. Soeradji Tirtonegoro. Data collection took place from April V, 2004 – May 30th, 2004. Results: The study shows that family perception in basic requirement fulfilment of human being at stroke patients pursuant to average value (mean) was fairly good with the average value equals 2,65. At some treatment actions the nurse role was not optimal because of the existence of disparity between family expectations with the reality of the nurse actions. Suggestion: Nurses who are involved with stroke patients must provide better service to patients and their family focusing on the basic requirement of the patients. Keywords: perception, family, nurse, role, basic requirement of human being